11p15 ICR1 Partial Deletions Associated with IGF2/H19 DMR Hypomethylation and Silver–Russell Syndrome. Issue 1 (26th October 2016) - Abi Habib, Walid; Brioude, Frederic; Azzi, Salah; Salem, Jennifer; Das Neves, Cristina; Personnier, Claire; Chantot‐Bastaraud, Sandra; Keren, Boris; Le Bouc, Yves; Harbison, Madeleine D.; Netchine, Irene
Abstract : Maternally inherited genetic defects affecting the OCT4‐binding site within the imprinting control region (ICR1) of the IGF2/H19 domain have been for long time associated with ICR1 hypermethylation in ∼20% of patients with Beckwith–Wiedemann syndrome. We report here the first paternally inherited deletions at the boundaries of the ICR1 associated with ICR1 hypomethylation in ∼1% of patients with Silver%Russell syndrome. These deletions are associated with hypomethylation of the ICR1 remaining CBS, and decreased IGF2 expression. ABSTRACT: The 11p15 region harbors the IGF2 / H19 imprinted domain, implicated in fetal and postnatal growth. Silver–Russell syndrome (SRS) is characterized by fetal and postnatal growth failure, and is caused principally by hypomethylation of the 11p15 imprinting control region 1 (ICR1). However, the mechanisms leading to ICR1 hypomethylation remain unknown. Maternally inherited genetic defects affecting the ICR1 domain have been associated with ICR1 hypermethylation and Beckwith–Wiedemann syndrome (an overgrowth syndrome, the clinical and molecular mirror of SRS), and paternal deletions of IGF2 enhancers have been detected in four SRS patients. However, no paternal deletions of ICR1 have ever been associated with hypomethylation of the IGF2/H19 domain in SRS. We screened for new genetic defects within the ICR1 in a cohort of 234 SRS patients with hypomethylated IGF2/H19 domain. We report deletions close to the boundaries of ICR1 on the paternal allele in one familial and two sporadic cases of SRS with ICR1 hypomethylation. These deletions are associated with hypomethylation of the remaining CBS, and decreased IGF2 expression. These results suggest that these regions are most likely required to maintain methylation after fertilization. We estimate these anomalies to occur in about 1% of SRS cases with ICR1 hypomethylation.